Pengaruh Bahasa Slang terhadap Penggunaan Bahasa Indonesia pada Komunikasi WhatsApp di Kelas F - Riva Sulsi Putri; Cinta Putri Syailin; Dara Yuniza Putri; Nurul Kurnia Ramadhani; Putri Nurhairin; Farel Olva Zufe (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to examine the influence of slang language usage on the use of Indonesian language in WhatsApp communication among students of Class F, Indonesian Language and Literature Education Study Program, Universitas Negeri Padang, academic year 2025/2026. This research employed a quantitative descriptive method with a correlational approach. The population and sample consisted of 35 students selected using total sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using descriptive analysis, Pearson correlation test, and simple linear regression. The results indicate that the use of slang language is categorized as high, while the use of standard Indonesian language is categorized as moderate. The correlation analysis shows a negative relationship between slang usage and the use of Indonesian language in WhatsApp communication. These findings suggest that higher intensity of slang usage tends to reduce the use of proper Indonesian language. This study is expected to raise students’ awareness of the importance of using appropriate Indonesian language according to communication contexts, particularly in academic settings.